Minding the Good Ground : A Theology for Church Renewal - Vickers, Jason E. (Book collections on Project MUSE., 2011)
Declining memberships. Pastoral scandals. A fear of secularism and the New Atheism. Christians are worried about the church's future. Despite such despair, Jason Vickers believes the church also sits upon the cusp of renewal. Some emerging voices promise to lead the church out of decay but focus only upon its structure, while others encourage the Spirit's work to the exclusion of all else. Minding the Good Ground organizes the multitude of voices and proposes a new way forward-rooting these renewal movements in a robust historical theology. Moving beyond quick-fix solutions, this new theological vision grounds renewal in the good and life-giving work of the Holy Spirit.